HUBUNGAN PENGETAHUAN DAN SIKAP DENGAN PERILAKU IBU HAMIL DALAM MELAKSANAKAN PEMERIKSAAN KEHAMILAN DIMASA PANDEMI CORONA VIRUS DISEASE 2019 (COVID-19) - Imelda Martina G Sianipar; Mawan Naibaho (JURNAL KESEHATAN INDRA HUSADA, 2022)
The non-natural disaster, COVID-19, has been declared as a global pandemic that impact on the high death rate. Maternal and neonatal health services are one of the affected terms in access and quality. It is feared that this leads to an increase in morbidity and mortality of mothers and newborns. Pregnant women have a higher risk of serious illness, higher morbidity and mortality than the general population. The purpose of this study was to analyze the relationship between knowledge and attitudes of pregnant women’s behavior in checking her pregnancy during the Covid-19 pandemic. The research method used a Cross Sectional Study, with population were pregnant women whom had Ante Natal Care at RSAB Harapan Kita - Jakarta. The number of samples were 50 pregnant women. Data Analysis used by chi-square test to looking for a relationship between knowledge and attitude variables and behavior variables. The results showed that was a low level of knowledge not related to behavior with a value of 0.493, but a positive attitude resulted in positive behavior with a value of 0.018. The result also shown, the factor related to the behavior of the mother in the implementation of Ante Natal Care was attitude. The conclusion of the study was there is no relationship between knowledge and behavior, but attitudes have a relationship with the behavior of pregnant women in checking their pregnancy at RSAB Harapan Kita - Jakarta Keyword : Covid-19, pregnant women, pregnancy, ante natal care